(untitled) (Educational Dimension, 2019)
Research goal: the research is aimed at the theoretical substantiation of the application of virtual reality technology simulators and their features in higher maritime educational institutions. Research objectives: to determine the role and place of simulation technology in the educational process in the training of future ship navigators in order to form the professional competence of navigation. Object of research: professional training of future ship navigators in higher maritime educational institutions. Subject of research: simulation technologies of virtual reality as a component of the educational process at higher educational maritime establishments. Research methods used: theoretical methods containing the analysis of scientific sources; empirical methods involving study and observation of the educational process. Research results: the analysis of scientific publications allows to define the concept of virtual reality simulators, their application in the training of future navigators, their use for assessing the acquired professional competence of navigation. Main conclusions: introduction of simulation technologies of virtual reality in the educational process in higher maritime educational institutions increases the efficiency of education, promotes the development of professional thinking of students, enhances the quality of professional competence development.